Variation in a Host–Parasitoid Interaction across Independent Populations - van Nouhuys, Saskya (Insects, 2012)
Antagonistic relationships between parasitoids and their insect hosts involve multiple traits and are shaped by their ecological and evolutionary context. The parasitoid wasp Cotesia melitaearum and its host butterfly Melitaea cinxia occur in several locations around the Baltic sea, with differences in landscape structure, population sizes and the histories of the populations. We compared the virulence of the parasitoid and the susceptibility of the host from five populations in a reciprocal transplant-style experiment using the progeny of five independent host and parasitoid individuals from each population. The host populations showed significant differences in the rate of encapsulation and parasitoid development rate. The parasitoid populations differed in brood size, development rate, pupal size and adult longevity. Some trait differences depended on specific host-parasitoid combinations, but neither species performed systematically better or worse in experiments involving local versus non-local populations of the other species. Furthermore, individuals from host populations with the most recent common ancestry did not perform alike, and there was no negative effect due to a history of inbreeding in the parasitoid. The complex pattern of variation in the traits related to the vulnerability of the host and the ability of the parasitoid to exploit the host may reflect multiple functions of the traits that would hinder simple local adaptation.